Exploring new avenues for Arene-Ruthenium complexes: coordination to [60]fullerene, hydrogen bonding assemblies and liquid-crystalline materials - Appavoo-Gupta, Divambal (My University, 2015)
The thesis aims at using arene-ruthenium complexes as building blocks for the synthesis of diverse compounds to obtain potential mesomorphic and/or biological properties. The thesis consists of three main projects.
The first project deals with supramolecular assemblies. New supramolecular di- and tetranuclear ruthenium arrangements, the latter bearing a cavity, were designed. H-bonding was the key interaction involved in the synthesis of the spacer ligands, which exist as dimers. Different spacer ligands and different ruthenium clips were used in synthesizing a whole family of the corresponding ruthenium assemblies/cages. Several analytical methods were employed to characterise the compounds and to study their arrangements.
The second project involves more classical ruthenium cages, including hexanuclear prisms and octanuclear cubes. Anthracene- and pyrene-core dendrimers were developed as potential guests, using key reactions such as click, Suzuki and Sonogashira coupling. Owing to the poor stability of the anthracene derivatives, their proper characterization and encapsulation could not be carried out. Pyrene derivatives showed better stability and were therefore studied further. The pyrene dendrimers, bearing cyanobiphenyl dendrons, displayed liquid-crystalline properties. Two pyrene dendrimers could be successfully encapsulated into hexanuclear arene-ruthenium prisms by the carceplex method. However, no mesomorphic properties were observed for the encapsulated systems.
The third project had as objective to study the biological properties of a system comprising of an arene-ruthenium moiety and [60]fullerene. Two such compounds were successfully synthesised. However, these compounds could not be tested for their potential biological activities because of their poor solubility in aqueous media.
Keywords: arene ruthenium, hydrogen bonding, liquid-crystal, fullerene Thèse de doctorat : Université de Neuchâtel, 2015
Keywords: arene ruthenium; hydrogen bonding; liquid-crystal; fullerene